2008
DOI: 10.1016/j.steroids.2008.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UDP-glucuronosyltransferase 1A10 in non-malignant and malignant human breast tissues

Abstract: UGT1A10 was recently identified as the major isoform that conjugates estrogens. In this study, realtime PCR revealed high levels of UGT1A10 and UGT2B7 in human breast tissues. The expression of UGT1A10 in breast was a novel finding. UGT1A10 and UGT2B7 mRNAs were differentially expressed among normal and malignant specimens. Their overall expression was significantly decreased in breast carcinomas as compared to normal breast specimens (UGT1A10: 68 ± 26 vs. 252 ± 86, respectively; p < 0.05) and (UGT2B7: 1.4 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Our results demonstrate that the mRNA levels of the UGTs analyzed, with the exception of UGT1A8, which was not expressed, are differentially down-regulated in breast cancers as compared to normal breast tissue specimen from AA and EA women in this study. This finding is in agreement with our published study in 2008 [16]. We also showed that UGT1A1 mRNA is significantly decreased in breast tumors compared to normal breast tissues.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our results demonstrate that the mRNA levels of the UGTs analyzed, with the exception of UGT1A8, which was not expressed, are differentially down-regulated in breast cancers as compared to normal breast tissue specimen from AA and EA women in this study. This finding is in agreement with our published study in 2008 [16]. We also showed that UGT1A1 mRNA is significantly decreased in breast tumors compared to normal breast tissues.…”
Section: Discussionsupporting
confidence: 94%
“…Estrogen metabolism by UGTs is the major drug-metabolic pathway that results in the complete inactivation of estrogens and their hydroxylated metabolites [912]. Alterations in UGTs, resulting in decreased UGT expression and glucuronidation activity towards estrogens and their metabolites, has been suggested to play a potential role in breast cancer risk [1416]. Our previous published study demonstrated that several UGTs, including UGT1A1, are involved in the complete inactivation of both native estrogens and their oxidative metabolites, including the genotoxic 4-OH-E1 [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations